Gambaran Pembelajaran Berbasis Developmentally Appropriate Practice (DAP) di Sekolah Dasar - Ganda Sari; Bertha Natalina Silitonga (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Learners are people who try to develop themselves through the education process. In the future they are the next generation of the nation who will run the Government as leaders. Therefore, the main focus of classroom teaching should be to help students develop and learn according to their development. The purpose of this study is to provide an overview of Developmentally Appropriate Practices (DAP) based learning in one of the public primary schools in Binong, Tangerang. To capture the learning, two indicators were used, namely teachers' beliefs about learners and learning practices in the classroom. The research method used a case study focusing on grade 1 with the subject of the homeroom teacher. The instruments used are questionnaires, interview guides, checklists and observation sheets for DAP-based classroom activities. The results showed that there is a congruence between teachers' beliefs about students and the principles of DAP, but in practice, teachers have not been optimal in practising DAP in the learning process. Suggestions for teachers are the need to improve their processional competence as teachers to seek knowledge about the characteristics of child development, teaching approaches or methods that are appropriate to the context, etc. Suggestions for schools are to provide adequate facilities for both teachers and students, provide guidance for and also activate the role of supervisors in schools.